Evaluasi Pelatihan Kepemimpinan Pada Karyawan PT Brantas Energi - Berlian, Mochammad Bayu; Laksono, Riyadi Dwi; Wahyuni, Vivi; Rusliana, Iu (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
The purpose of this research is to find out how effective the leadership training with the theme "leading a team and leading a business" is for employees of PT Brantas Energi. This training is intended to provide leadership knowledge within 4 days. This research was conducted quantitatively, and primary data was collected from the pretest and post-test scores of 26 respondents. Data were tested by descriptive analysis and paired t-test. The results showed that there was a significant difference between the scores of the pretest and post-test participants. This shows that the average score of the participants increased after attending the training. In addition, the significance value shown by the Wilcoxon Matched-Pairs test analysis showed that the participants' knowledge increased after participating in the training. Overall, the findings of this study indicate that the training materials increased participants' knowledge and understanding of leadership.